A Concise Review of Home Health Care Routing and Scheduling Problem - Soumen Atta; Vítor Basto-Fernandes; Michael Emmerich (Operations Research Perspectives, 2025)
The Home Health Care Routing and Scheduling Problem (HHCRSP) plays a crucial role in optimizing the delivery of home-based healthcare services by efficiently allocating caregivers to patient locations while adhering to logistical, operational, and regulatory constraints. This concise review provides an analysis of HHCRSP, discussing its key objectives, constraints, and solution methodologies. The study examines various optimization approaches, including exact algorithms, heuristics, and metaheuristic techniques. Furthermore, the impact of HHCRSP on healthcare delivery efficiency is explored, highlighting its role in reducing operational costs, improving service quality, and ensuring continuity of care. The article also discusses the regulatory requirements affecting HHCRSP, addressing compliance with legal and organizational requirements, quality assurance frameworks, economic constraints, and patient prioritization mandates. The challenges associated with HHCRSP, including logistical complexities, workload balancing, and technological barriers, are also reviewed. To align HHCRSP with regulatory frameworks, this review discusses various strategies such as adaptive scheduling, advanced algorithmic solutions, and the integration of environmental and social sustainability considerations. Additionally, emerging technological advancements, including the use of Artificial Intelligence (AI), Internet of Things (IoT), and intelligent transport systems, are evaluated for their potential to enhance HHCRSP efficiency. The article concludes by summarizing key findings, discussing the practical implications of HHCRSP for healthcare providers, and outlining future research directions. Addressing existing gaps, such as AI explainability, blockchain integration for secure scheduling, and sustainable healthcare logistics, remains a critical avenue for further exploration. As the demand for home healthcare services grows, innovative HHCRSP solutions will be essential to ensuring high-quality, cost-effective, and patient-centered care.